Production and characterization of halal-based gelatin derived from Red Nile Tilapia (Oreochromis niloticus) fishbone - Rahmayanti, Mayu; Irsyadulibad, Mohamad; Dewi, Tanaya Jati Dharma; Firdausi, Amalia Salsa Billah; Megawati, Dewi Sinta; Jebreen, Ali (Universitas Ahmad Dahlan, 2025)
Gelatin is one of the chemical products derived from protein hydrolysis. The demand for gelatin in Indonesia increases yearly, but domestic production still needs to meet the demand, leading to imports. International gelatin production statistics indicate that 58% is derived from pig skin, which is prohibited for Muslims. Therefore, this research aims to produce halal-based gelatin that meets quality standards. Red Nile Tilapia (Oreochromis niloticus) fishbones are used as the raw material for this study, as their halal status is clear in the Quran and Hadith. The fishbones are soaked in different concentrations of phosphoric acid, namely F1 (4%), F2 (6%), and F3 (8%), for 48 hours, then extracted using distilled water solvent in a water bath for 6 hours. The extracted solution is filtered, and the filtrate is dried in an oven at 50°C for 48 hours. The gelatin yield is statistically analyzed using correlation methods, and its functional groups are identified using FTIR spectroscopy. Compared to existing standards, gelatin characteristics are evaluated through organoleptic tests, such as pH, gel strength, viscosity, moisture content, and ash content. The gelatin yield for F1 is 8.15 ± 0.18%; F2 is 12.08 ± 0.12%, and F3 is 15.66 ± 0.26%. The research demonstrates that phosphoric acid concentration significantly influences gelatin yield, with higher concentrations resulting in higher yields. The FTIR spectra also indicate that the synthesized gelatin resembles commercial gelatin in spectra and absorption peaks. All gelatin variations meet the requirements for organoleptic properties, gel strength, moisture content, and ash content, while only F1 and F2 meet the pH requirements. Keywords: FTIR, halal gelatin, Red Nile Tilapia (Oreochromis niloticus) fishbone.